An alternative way to encapsulate probiotics within electrospun alginate nanofibers as monitored under simulated gastrointestinal conditions and in kefir - Yilmaz, Mustafa Tahsin; Taylan, Osman; Karakas, Canan Yagmur; Dertli, Enes (ELSEVIER SCI LTD, 2020)
In this study, Lactobacillus paracasei KS-199 was encapsulated within alginate-based electrospun nanofiber mats possessing uniform, well-defined, smooth and bead-free structure with an average size of 305 nm in diameter. Enhanced protection ability of the mats was observed in thermal degradation assays (weight loss from 93.4 to 84.5%). Probiotic and in situ viabilities were determined in simulated gastrointestinal and in vitro conditions, respectively, demonstrating that nanoencapsulation of the strain could enhance its survival in simulated gastric juice (the viability rate from 64.1 to 70.8 log cfu/mL) and improved its viability/survival (from 6.65 to 7.38 log cfu/mL) in kefir, respectively. Inoculation of kefir with encapsulated strain did not change the characteristic pseudoplastic flow behavior and viscoelastic nature (being predominantly elastic than viscous; G' > G '' values) of kefir. Given these results, it is possible to suggest that alginate can be an important tailor-made biopolymer playing an essential role for encapsulation of probiotics with increased viability.
Keywords: Nanoencapsulation by electrospinning; Alginate; Lactobacillus; In vitro/in situviability; simulated gastrointestinal conditions; RHEOLOGICAL BEHAVIOR; IMPROVED SURVIVAL; MICROENCAPSULATION; BACTERIA; VIABILITY; BIFIDOBACTERIA; CHEESE; MATS; IDENTIFICATION; ACIDOPHILUS; Chemistry; Polymer Science